The relationship between adolescents´ chronotype and depressive symptoms : the mediating role of sleep - Agnes Ýr Óskarsdóttir 1999- (2022)
Studies have reported that evening chronotypes (i.e. individuals that have the natural tendency to fall asleep late in the evening) show more symptoms of depression as well as having worse sleep quality. It remains controversial whether chronotype has direct effect on depressive symptoms or indirect through its impact on other factors, such as sleep. The current study examined the relationship between chronotype and depressive symptoms and investigated whether sleep mediated the relationship between eveningness and depressive symptoms. The present study was cross-sectional and participants were 113 upper-secondary school students from Reykjavik. The results showed that sleep was associated with both chronotype and depressive symptoms. Adolescents who were more evening prone had worse sleep quality than morning types, as well as those who had worse sleep quality showed more symptoms of depression. The main findings indicated that chronotype does not directly affect depressive symptoms but it indirectly affects depressive symptoms through its impact on sleep quality. Finding the mediating pathway suggests that interventions aimed at increasing sleep quality will reduce depression, such as circadian stimulating light therapy. Further studies are needed to understand the nature of the association. Keywords: chronotype, depressive symptoms, sleep quality, adolescents Rannsóknir hafa sýnt að einstaklingar með kvölddægurgerð (þ.e. einstaklingar sem hafa náttúrulega tilhneigingu til að sofna seint á kvöldin) sýni meiri þunglyndiseinkenni en morgundægurgerð, auk þess að hafa verri svefngæði. Það er umdeilt hvort dægurgerð hafi bein áhrif á þunglyndiseinkenni eða óbein áhrif í gegnum áhrifin sem það hefur á aðra þætti, t.d. svefn. Í þessari rannsókn var sambandið á milli kvöldgerðar og þunglyndiseinkenna skoðað, auk þess var kannað hvort svefn miðli sambandinu. Rannsóknin var þversniðsrannsókn og voru þátttakendurnir 113 framhaldsskólanemar á fyrsta ári frá Reykjavík. Niðurstöðurnar sýndu að marktækt samband var á milli ...